2017
DOI: 10.1088/1674-1056/26/7/078901
|View full text |Cite
|
Sign up to set email alerts
|

Feedback arcs and node hierarchy in directed networks

Abstract: Directed networks such as gene regulation networks and neural networks are connected by arcs (directed links). The nodes in a directed network are often strongly interwound by a huge number of directed cycles, which lead to complex information-processing dynamics in the network and make it highly challenging to infer the intrinsic direction of information flow. In this theoretical paper, based on the principle of minimum-feedback, we explore the node hierarchy of directed networks and distinguish feedforward a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 42 publications
(136 reference statements)
1
14
0
Order By: Relevance
“…The total arc energy of a valid configuration h is defined as the total number of feedback arcs in this configuration. We should emphasize that, different from the model introduced in [4], a horizontal arc between two vertices of the same layer costs no energy in the D-segmentation problem. An optimal solution for the D-segmentation problem is a valid configuration h whose arc energy achieves the global minimum value.…”
Section: Modelmentioning
confidence: 98%
See 3 more Smart Citations
“…The total arc energy of a valid configuration h is defined as the total number of feedback arcs in this configuration. We should emphasize that, different from the model introduced in [4], a horizontal arc between two vertices of the same layer costs no energy in the D-segmentation problem. An optimal solution for the D-segmentation problem is a valid configuration h whose arc energy achieves the global minimum value.…”
Section: Modelmentioning
confidence: 98%
“…For example, in Fig. 1 the directed path formed by arcs (1,5), (5,3), (3,4), (4,2), and (2, 1) is a directed cycle of length five connecting all the vertices of the digraph.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The element of B is where δ jk = 1 if j = k, and δ jk = 0 otherwise. Recent studies showed that the dynamic message-passing approach predicts the epidemic spreading dynamics well on uncorrelated locally tree-like networks [56], and it has found wide applications in epidemic containment [52], locating spreading sources [57], and network dismantling [58]. However, the dynamic message-passing approach needs 2E + N differential equations, which is time-consuming for large networks.…”
Section: Theoretical Approachesmentioning
confidence: 99%